1975
DOI: 10.1007/bf02545077
|View full text |Cite
|
Sign up to set email alerts
|

Processing soybeans into foods: Selected aspects of nutrition and flavor

Abstract: Since many new soy protein products are being developed which differ in enzyme activity, protein dispersibility, flavor, nutritive value, and functional properties, quality control is assuming increasing significance. The effects of dry and moist heat and hexane:ethanol azeotrope extraction upon various enzymatic activities, protein solubility, and nutritive value of defatted soy flakes differ considerably. Specifications and guidelines initially developed to establish the degree of moist heat treatment requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
2

Year Published

1981
1981
2005
2005

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 9 publications
2
22
0
2
Order By: Relevance
“…Maximum growth occurs in rats fed soy diets in which only 79% of the TI activity was eliminated by live steam treatment, and pancreatic hypertrophy did not occur with only 54% destruction of TI (49). Biochemical threshold level effects in long-term rat feeding studies confirm these findings (50).…”
Section: Antinutritional Factors and Protein Quality Of Soybeans Withsupporting
confidence: 68%
“…Maximum growth occurs in rats fed soy diets in which only 79% of the TI activity was eliminated by live steam treatment, and pancreatic hypertrophy did not occur with only 54% destruction of TI (49). Biochemical threshold level effects in long-term rat feeding studies confirm these findings (50).…”
Section: Antinutritional Factors and Protein Quality Of Soybeans Withsupporting
confidence: 68%
“…Radiation of seeds prior to soaking results in even greater destruction of TI without affecting the protein content. It has been reported that 70-80 % of TIA in soybean needed to be destroyed in order to achieve maximum gain in weight and PER with rats [23]. In this connection, it is important to note that there are significant varietal differences [24], which may influence the effectiveness of autoclave inactivation of TIA, the treatment which is believed to destroy almost 80 % of the TIA in most legumes.…”
Section: Resultsmentioning
confidence: 98%
“…Isolated soy proteins have found widespread application in forrnulated food products, and are also used directly as nutritional supplements (Rackis et al, 1975).…”
Section: Fats and Oilsmentioning
confidence: 99%